205k views
4 votes
What is the sum of the polynomials? (7x^3 – 4x^2) + (2x^3 – 4x^2) 5x^3 9x^3 5x^3 – 8x^2 9x^3 – 8x^2

2 Answers

4 votes

Answer:


\large\boxed{9x^3-8x^2}

Explanation:


(7x^3-4x^2) + (2x^3-4x^2)\\\\=7x^3-4x^2+2x^3-4x^2\\\\\text{combine like terms}\\\\=(7x^3+2x^3)+(-4x^2-4x^2)\\\\=9x^3-8x^2

User Kevin Grant
by
5.3k points
5 votes

Answer:

9x^3 - 8x^2

Explanation:

Let's simplify step-by-step.

7x^3−4x^2+2x^3−4x^2

=7x^3+−4x^2+2x^3+−4x^2

Combine Like Terms:

=7x^3+−4x^2+2x^3+−4x^2

=(7x^3+2x^3)+(−4x^2+−4x^2)

=9x^3+−8x^2

I hope this helps you ! :))

User Der Kommissar
by
5.2k points